DOES SERUM C-REACTIVE PROTEIN HAVE CORRELATION WITH THE SEVERITY OF ACUTE ISCHEMIC STROKE? - Salma, Kayla Maritza Putri; Rakhmatiar, Rodhiyan; Eko Arisetijono Marhendraputro (Journal of Pain, Headache and Vertigo, 2025)
Background: Ischemic stroke can trigger an inflammatory response in the body. C-Reactive Protein is a biomarker that is elevated during inflammation. There is various evidence about correlation between CRP levels and the severity of ischemic stroke. Objective: To identify the correlation of CRP levels with stroke severity based on the National Institutes of Health Stroke Scale (NIHSS). Methods: A descriptive retrospective analytic study was used, and data were obtained from medical records of acute ischemic stroke patients in the Neurology Department of Saiful Anwar Hospital for 3 years. Subject characteristics analyzed were CRP levels, severity of ischemic stroke based on the NIHSS scale, and risk factors of ischemic stroke (age, gender, blood pressure, atrial fibrillation, infection, and random blood sugar). CRP levels and NIHSS scale were compared using Mann Whitney comparison test. Results: Out of 332 patients, 39 patients met the inclusion criteria. The amount of patient above 55 years old was 22 people (56.41%). The gender ratio was 19 men (48.72%) and 20 women (51.28). In the risk factor section, 35 people (89.74%) had hypertension, 11 people (28.21%) had atrial fibrillation, 17 people (43.59%) had infections, and 5 people (12.82%) had high random blood sugar. The comparison test showed that there was an increase in CRP levels along with the severity of stroke according to NIHSS mild-moderate and severe-very severe (p = 0.701). Conclusion: There is no significant relationship between CRP levels and the severity of stroke based on NIHSS.